The Recovery from Alcohol Consumption: Analysis of the Construct of Relapse - Hugo E. Reyes-Huerta; Ángeles Vacio; Francisco Pedroza; Martha Salazar; Kalina Martínez (International Journal of Psychological Research, 2018)
Objective: A systematic review was conducted to identify definitions that facilitated the study of relapse as both behavioral pattern and process. Methods: The review was conducted following the PRISMA-P guidelines. Articles that met the following inclusion criteria were considered: (a) published in peerreviewed journals, (b) provided an explicit operational definition of relapse, (c) assessed relapse during or after a specific psychological or self-care group intervention, (d) focused on alcohol consumption, and (e) were published between 2000 and September 2016. Results: “Any drinking” was the most frequent outcome used to identify relapse, although other discrete outcomes were also considered. Nevertheless, none of the definitions operationalize the notion of the return to a problematic drinking pattern and/or the process of relapse. Conclusion: Problems related to any drinking definition are discussed and we propose the use of a composed index to study relapse.